Trauma, race, and risk for violent felony arrests among Florida juvenile offenders - Johnson, Micah E. (Crime & delinquency, 2018)
This study tests the assumptions of the The Childhood Trauma Model, which proposes that marginalized populations are both more likely to have traumatic childhoods and more criminalized than those in the upper echelons of society. It hypothesizes that traumatic childhood experiences increase risk of being sanctioned for violent behavior, and risks are amplified for minority and disadvantaged groups. The study finds that experiencing three or more traumas had a 200% to 370% increased chance of being arrested for a violent felony as youth who experienced a single traumatic event, and Blacks had up to 300% increased risk than Whites with equal trauma scores.